Resilience Predicts Self-Stigma and Stigma Resistance in Stabilized Patients With Bipolar I Disorder - Post, Fabienne; Buchta, Melanie; Kemmler, Georg; Pardeller, Silvia; Frajo-Apor, Beatrice; Hofer, Alex (Frontiers in Psychiatry, 2021)
The identification of factors that prevent self-stigma and on the other hand promote stigma resistance are of importance in the long-term management of bipolar disorder. Accordingly, the aim of the current study was to investigate the association of factors deemed relevant in this context, i.e. resilience, premorbid functioning, and residual mood symptoms, with self-stigma/stigma resistance. 60 patients diagnosed with bipolar I disorder were recruited from a specialized outpatient clinic. Self-stigma and stigma resistance were measured by the Internalized Stigma of Mental Illness (ISMI) Scale. The presence and severity of symptoms were assessed by the Montgomery-Asberg Depression Rating Scale (MADRS) and the Young Mania Rating Scale (YMRS). Resilience and premorbid functioning were measured by the Resilience Scale (RS-25) and the Premorbid Adjustment Scale (PAS), respectively. Resilience correlated negatively with self-stigma and positively with stigma resistance and was a predictor for self-stigma/stigma resistance in multiple linear regression analysis. Residual depressive symptoms correlated positively with self-stigma and negatively with stigma resistance. There were no significant correlations between sociodemographic variables, premorbid functioning as well as residual manic symptoms and self-stigma/stigma resistance.The findings of this study implicate that resilience may be considered as an important component of self-stigma reduction interventions.